(untitled) (Colloquia Comparativa Litterarum, 2025)
The article examines current trends in the development of South Slavic comparative literary studies. The discussion revolves around the reviewing of the notion of a South Slavic literary community and a unified South Slavic literary process. Interpretation focuses on the comparison of the Yugoslav and Post-Yugoslav literary contexts. Reference is made to the affiliation of South Slavic literatures to various cultural regions. The author comes to the conclusion that there is a need for a reviewing of South Slavic literatures as an open construction and a dynamic field of identities.